Rock fracturing using expansive mortar - Ong, Jun Kai (Nanyang Technological University, 2024)
Controlling of rock fracturing under stress wave loading is important to mitigate the negative impacts of underground excavation such as safety hazards and environmental pollution, with rock failure commonly occurring during the drill and blast method for excavation in Singapore. This study is built on the usage of expansive mortars to control rock fracturing. Finite Element Method (FEM) software is used to model the pressure distribution on the rock sample and aim to dive further into understanding how the failure pattern is developed and to support empirical evidence with numerical analysis using FEM modelling. It was discovered that the rock samples fracture initially with two cracks on opposite ends of a sample rock borehole under tensile failure corroborating with the strain analysis done on ANSYS. Modelling was also done on granite and limestone samples while varying the Young’s Modulus, where average values, upper bound and lower bound values for the Young’s Modulus were considered. The modelling strain results generally corroborate with the experimental values, with granite having a maximum error of 17%, while limestone has a much lower maximum error of 6%. However, due to limitations in FEM software and imperfections of the rock samples. Further studies and experiments should be conducted to ensure the optimal control of the rock fracturing process before the mortars can be used for field usage.